(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Exposure to polycyclic aromatic hydrocarbons (PAHs) can cause many genetic alterations, which may contribute to cancers because PAHs derivatives can bound to DNA induces mutations and tumorigenesis. Some cancer-related proteins differentially expressed in exposed workers such as Human epididymal protein 4 (HE4) therefore, it considers a good biomarker for PAHs adverse effects that can progressed to tumors. Objective: To estimate HE4 level in refinery workers to predict related adverse effect of PAHs that can developed to occupational cancer. Methods: This study included 168 participants divided in three groups (control, office workers and in field workers). PAHs and HE4 were measured for each participant by GC/MS, ELISA respectively. Results: PAHs were negative in controls blood whereas they were elevated in office and field workers. Concentration of HE4 was significantly higher in field than in office workers and controls, as well as significant correlation between concentration of PAHs and HE4 levels with duration of exposure was found. Conclusion: PAHs and HE4 levels were significantly increased in refinery exposed workers (both field and office workers). Keywords: Polycyclic aromatic hydrocarbon, air pollution, Human epididymal protein4, mutation, tumor marker Citation: Shaker AW, Al-Wasiti EA. The Association between human epididymal protein 4 and exposure to poly aromatic hydrocarbons in samples of Al-Daura Refinery Workers-Baghdad. Iraqi JMS. 2023; 21(1): 23-29. doi: 10.22578/IJMS.21.1.3